Effect of feeding yearling steers on bluestem pasture 2 pounds of corn or soybean pellets during the latter part of the grazing season. - Smith, E.F.; Baker, F.H.; Cox, R.F.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
Thirty-six head of good quality yearling Hereford steers were used in this test. They had been grazing together on bluestem pasture previous to the test. The steers were divided into three lots of 12 steers each, in a manner to equalize any difference due to previous winter treatments. They were grazed on bluestem pasture and received the following treatment from August 6, 1953, to October 23, 1953. Lot I-No supplement. Lot 2-Two pounds of soybean pellets per head daily. Lot 3-Two pounds of corn per head daily. The steers were rotated on the pastures every 15 days to equalize any differences that might be due to pastures.
Keywords: Beef; Steers; Bluestem pasture; Gain; Protein